Environmental DNA Metabarcoding Reveals the Eukaryotes Diversity in Marine Protected Area of Lombok Island, Indonesia - Pratomo, Arief; Bengen, Dietriech Geoffrey; Zamani, Neviaty Putri; Madduppa, Hawis (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2022)
Biodiversity assessment surveys are necessary for establishing conservation areas. However, such surveys are typically expensive, primarily if they cover a large area and take a long time. The survey difficulty increases when applied to cryptic, sparse, and fast-moving organisms. In addition, it requires expertise in taxonomic-biota classification. The breakthrough environmental DNA (eDNA) metabarcoding technique promises to overcome all the hurdles of assessing the potential for marine biodiversity in a non-invasive, rapid, extensive, and more effective way. We evaluated the ability of the eDNA survey to reveal the potential diversity and character of marine eukaryotes in the Lombok Island Marine Protected Area. A sampling of seawater and sediment eDNA in pore size fractions of 0.4-12 ?m and >12 ?m was carried out in the Core Zone, Non-Core Zone, and Non-Conservation Area, in east, north, and west Lombok, respectively. The detection and classification of eukaryotes using bioinformatics analysis were accomplished following extraction, amplification, and DNA sequencing. We identified 20,478 unique sequences of potential species classified in five kingdoms to 654 marine eukaryotes families. The comparison results show differences in community structure between locations, as well as differences in diversity between media and factions. The eDNA survey can assess marine biodiversity at a macro level and has implications for management in conservation areas.Keywords: Biodiversity, Marine eukaryotes, environmental DNA, the Primary V9-SSU 18S rRNA gene